Navigating Challenges and Inclusivity: Unveiling the Gender Perspective in Contemporary Gender Politics - Muhammed Sufyan V.V (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
Gender politics is a critical field of study that examines the power dynamics, social structures, and policy frameworks that influence and are influenced by notions of gender. This abstract provides an overview of the gender perspective within gender politics and delves into the challenges it encounters. Gender politics scrutinizes how societal norms, cultural expectations, and institutional arrangements shape individuals' roles and experiences based on their gender identity. By analyzing the intersections of gender with other axes of identity, such as race, class, and sexuality, gender politics seeks to expose inequalities and promote inclusivity. However, gender politics faces multifaceted challenges in its pursuit of equality and justice. One key challenge is the resistance to change from individuals and institutions invested in maintaining traditional power dynamics. Pushback against gender-inclusive policies, women's leadership, and LGBTQ+ rights underscore the deeply ingrained nature of these challenges. The struggle to dismantle ingrained stereotypes and gendered expectations poses another hurdle. Prevailing narratives that associate masculinity with strength and femininity with passivity can perpetuate discrimination and limit individuals' opportunities, reinforcing harmful binaries. Overcoming these narratives requires concerted efforts in education, media representation, and public discourse. Furthermore, navigating the global nature of gender politics presents complexities. Different cultures, histories, and levels of development result in diverse gender-related issues across societies. While some regions make strides in gender equality, others grapple with basic rights and access to resources, necessitating tailored approaches within a universal framework. The digital age introduces both opportunities and challenges for gender politics. Online platforms can amplify marginalized voices and facilitate organizing, but they also expose individuals to cyberbullying, harassment, and harmful stereotypes. Balancing the positive potential of technology with its negative consequences requires ongoing attention. The struggle for gender equality also intersects with economic disparities. Gender pays gaps, unequal distribution of unpaid care work, and limited access to economic resources disproportionately affect women and marginalized gender identities. Addressing these economic aspects is pivotal for achieving comprehensive gender justice. In conclusion, the gender perspective within gender politics critically analyzes power dynamics and strives for equitable representation and treatment. The challenges it faces, ranging from resistance to change and entrenched stereotypes to global variations and technological impacts, necessitate collaborative efforts across academia, activism, policy-making, and society at large. By acknowledging and addressing these challenges, gender politics can contribute to reshaping societies into more inclusive, just, and equal spaces for all genders.